2018
DOI: 10.1007/s00248-018-1158-4
|View full text |Cite
|
Sign up to set email alerts
|

A Crispy Diet: Grazers of Achromatium oxaliferum in Lake Stechlin Sediments

Abstract: Achromatium is the largest freshwater bacterium known to date and easily recognised by conspicuous calcite bodies filling the cell volume. Members of this genus are highly abundant in diverse aquatic sediments and may account for up to 90% of the bacterial biovolume in the oxic-anoxic interfaces. The high abundance implies that Achromatium is either rapidly growing or hardly prone to predation. As Achromatium is still uncultivated and does not appear to grow fast, one could assume that the cells might escape p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…2b,3b,4b,S3,and S4b). Most recently, a study on grazers of Achromatium in freshwater Lake Stechlin in Germany noticed that meiofaunal predators only hunt the smallest Achromatium cells and store them in their low-pH food vacuoles, presumably for calcite dissolution (Schorn and Cypionka 2018). Apparently, hardto-digest calcite inclusions combined with large cell size provides Achromatium with some protection against meiofaunal grazing.…”
Section: Discussion: a Scenario For Calcite Granule Dynamicsmentioning
confidence: 99%
“…2b,3b,4b,S3,and S4b). Most recently, a study on grazers of Achromatium in freshwater Lake Stechlin in Germany noticed that meiofaunal predators only hunt the smallest Achromatium cells and store them in their low-pH food vacuoles, presumably for calcite dissolution (Schorn and Cypionka 2018). Apparently, hardto-digest calcite inclusions combined with large cell size provides Achromatium with some protection against meiofaunal grazing.…”
Section: Discussion: a Scenario For Calcite Granule Dynamicsmentioning
confidence: 99%
“…Antagonism between bacteria and fungi has been shown to be often connected to direct resource competition 125 . Recently, even direct trophic interactions between the largest freshwater bacterium Achromatium and chytrid fungi have been observed 126 (FIG. 4).…”
Section: Box 1: Biotic Interactions With Aquatic Fungimentioning
confidence: 99%
“…(2015) analyzed Ca‐carbonate granules in situ within Achromatium cells by Raman microspectroscopy and also concluded that they were calcite crystals. Consistently, most recent studies assumed that intracellular granules were calcite crystals based on the latest reports in the literature (e.g., Babenzien et al, 2015; Ionescu et al., 2017; Mansor et al., 2015; Schorn & Cypionka, 2018; Yang et al., 2019). Yet, the observations by West and Griffiths (1913) suggesting that Achromatium CaCO 3 granules are composed of ACC seem precisely documented.…”
Section: Introductionmentioning
confidence: 73%